ANALISIS AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA BAWANG SAKTI JAYA KABUPATEN TULANG BAWANG - Achmad Suharyo; Kurniati Kurniati (Universitas Bandar Lampung (UBL), 2019)
Management of village funds requires an aspect of good governance where one of the pillars is accountability. It is hoped that a large enough village fund will have a significant impact on the welfare of the village community, and can truly be reported and accounted for. Village financial management is carried out based on governance principles, namely transparent, accountable and participatory. This research was conducted in Bawang Sakti Jaya Village in the area of Tulang Bawang Regency. With the number of informants 20 (twenty) people, namely the Assistant Inspector Region 1, Young Auditor, Camat, District Secretary, Village Officials, Community Leaders, LPMD, Female Leaders, BPD.This research uses descriptive qualitative method. The method used is the method used is content analysis and technical analysis used is reduction, data presentation and drawing conclusions. The results of this study indicate that the accountability of village fund management in Bawang Sakti Jaya Village has been implemented based on transparent, accountable and participatory principles. In reporting and accountability, it has been carried out in accordance with the mechanism based on the provisions, although there are still negligence from village officials and technical managers of activities. Competence of management resources is still a major obstacle, so that local government assistance is still needed. To increase accountability in the management of village funds in Bawang Sakti Jaya Village, continuous guidance, training, monitoring and evaluation are needed for village officials.